Análise das soluções de drenagem propostas para redução das áeras de risco à inundações em Iguatu-Ce - Oliveira, Lorayne Queiroz de (2025)
Urban flooding is one of the major challenges faced by Brazilian cities, particularly in semi- arid regions such as Iguatu, in the state of Ceará, where the intensity of rainfall combined with unplanned urbanization increases hydrological and social risks. This study aims to analyze drainage solutions for reducing flood-prone areas in Iguatu-CE, with a focus on the neighborhoods of Cajueiro, Alvorada, and Areias I and II, crossed by the Julião stream. To achieve this, hydrological and hydraulic studies were conducted based on rainfall data from stations 639001, 639035, 639038, and 639058, using established methods such as the Triangular Unit Hydrograph, the Rational Method, and IDF curves obtained through the disaggregation of daily rainfall. Modeling was carried out using Civil 3D software and the C3DRENESG plugin, enabling proper sizing of the drainage network. Three alternatives for the redirection of the Julião stream were compared through a multi-criteria analysis, considering technical, economic, environmental, and social criteria. The results indicate that the selected alternative is technically feasible and environmentally more suitable for the watershed conditions, significantly contributing to the mitigation of the impacts of intense rainfall. Finally, the study reinforces the importance of urban planning and continuous monitoring to ensure the long-term effectiveness of drainage systems in vulnerable urban areas.